2019
DOI: 10.1177/1756829319841817
|View full text |Cite
|
Sign up to set email alerts
|

Passive stability enhancement with sails of a hovering flapping twin-wing robot

Abstract: Hovering flapping wing flight is intrinsically unstable in most cases and requires active flight stabilization mechanisms. This paper explores the passive stability enhancement with the addition of top and bottom sails, and the capability to predict the stability from a very simple model decoupling the roll and pitch axes. The various parameters involved in the dynamical model are evaluated from experiments. One of the findings is that the damping coefficient of a bottom sail (located in the flow induced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…The damping constant K is easily evaluated by a pendulum experiment. 17 Here, we include the rotary damping:…”
Section: Modelling and Control Body Dynamics Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The damping constant K is easily evaluated by a pendulum experiment. 17 Here, we include the rotary damping:…”
Section: Modelling and Control Body Dynamics Modelmentioning
confidence: 99%
“…Figure 17 shows the sensitivity to z d when it varies from À5 mm to þ5 mm. Although z d has a determinant influence on the open-loop behavior of the system, 17 its influence on the closed-loop poles seems more moderate, provided it remains in reasonable limits; the system experiences a divergent instability if z d 5 À 9 mm. The influence of the time constant T of the actuator is analyzed in Figure 18; one sees that the location of the oscillatory poles is strongly dependent on the time constant T of the wing twist actuators.…”
Section: Control Stability and Sensitivitymentioning
confidence: 99%
“…But, importantly, via experimental study on such tail, we found that the lift and pitch moment was proportional to the tail position, which promoted us to study further on different tails. Also, such kind of the tail was successfully applied to the passive stability of flying [35].…”
Section: Figurementioning
confidence: 99%
“…For example, periodic motion parameters should be used, the spring stiffness should be increased if anti-disturbance performances of the robot are weak, some measures should be taken to reduce the shaking of the mass center and the disturbance amplitude. As far as I know, these suggestions have rarely studied [44][45][46]. Though the above conclusions have been obtained, the following aspects should be further studied in the future: (1) A complex dynamic model should be established to approach the real robot under randomly uncertain disturbances, and a method should be proposed to solve the contradiction between the model complexity and the calculation feasibility; (2) Some quantitative conclusions, e.g., the influence mechanism curves of the disturbances on the robot performances, should be further studied; (3) Some other experiments under randomly uncertain disturbances, e.g., wind tunnel experiments, vibration and friction experiments, should be carried out in the future.…”
Section: Plos Onementioning
confidence: 99%